Production of biomass by Schizophyllum commune and its antifungal activity towards rubberwood-degrading fungi - Teoh, Yi Peng; Mashitah Mat Don,; Salmiah Ujang, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Rubberwood is the most popular timber for furniture manufacturing industry in Malaysia. Major drawback concerned that rubberwood is very prone to attack by fungi and wood borers, and the preservation method using boron compounds exhibited hazardous effect to the workers. Fungal-based biological control agents have gained wide acceptance and Schizophyllum commune secondary metabolite played an important role in term of antifungal agent productivity. The effects of initial pH, incubation temperature and agitation on biomass production by S. commune were investigated under submerged shake culture. In this work, it was found that the synthetic medium with initial solution pH of 6.5 and incubated at 30ºC with shaking at 150 rpm provided the highest biomass production. The biomass extract from S. commune was then applied onto the rubberwood block panel to investigate its effectiveness. The results showed that biomass extract at a concentration of 5 μg/μL could inhibit the growth of selected rubberwood-degrading fungi, such as Lentinus sp., L. strigosus and Pycnoporus sanguineus.